Primary health care professionals' practice in the face of leprosy: a scoping review - Michelle Santos Macêdo; Nanielle Silva Barbosa; Priscilla Dantas Almeida; Júlia Oliveira Melo; Jonas Alves Cardoso; Telma Maria Evangelista de Araújo (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to identify Primary Health Care professionals' practice in the face of leprosy. Methods: a scoping review, carried out between November 2022 and January 2023, conducted according to the methodological structure proposed by JBI and checklist Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews in six databases and additional literature. Results: the sample consisted of 11 articles, published between 2008 and 2022. The findings were synthesized into three categories: Early diagnosis and timely treatment; Physical disability prevention; and Household and social contact surveillance. Final Considerations: there is a need to align the practices carried out with those recommended by the Brazilian National Program for Leprosy Control and Elimination, as some were not identified in studies, which implies losses to qualified assistance directed to patient demands, with a view to control and elimination of leprosy.